Control of active lubrication for hydrostatic journal bearing by monitoring bearing clearance - Waheed Ur Rehman; Guiyun Jiang; Yuanxin Luo; Yongqin Wang; Wakeel Khan; Shafiq Ur Rehman; Nadeem Iqbal (Advances in Mechanical Engineering, 2018)
Active hydrostatic journal bearings represent a mechatronic answer to the fast-growing industrial needs to high-performance rotary machineries. The aim of this research is to study and improve the dynamic characteristics of hydrostatic bearing, with four pockets or recess. In order to improve dynamic characteristics for hydrostatic journal bearing, this research presents an active hydrostatic journal bearing with servo control. The results of active hydrostatic journal bearing with servo control were compared with those of traditional hydrostatic journal bearing with capillary throttling. The dynamic characteristics of the newly proposed bearing and traditional bearing are studied and compared under different dynamic conditions such as variable speed, viscosity, load, pressure, and bearing clearance. The numerical result shows that the proposed active hydrostatic journal due to active lubrication has good performance including stability and controllability, high stiffness, faster response, and strong resistance. Furthermore, two strategies such as proportional–integral–derivative and integrator backstepping control are also presented to improve the performance and efficiency of active hydrostatic journal bearing with servo control. The result shows that integrator backstepping control is more effective than proportional–integral–derivative control in terms of faster response and greater amplitude reduction, quickly regaining equilibrium position, and good stiffness against load. Hence, it is observed that active lubrication in hydrostatic journal bearing provides us better dynamic characteristics which will have potential applications in heavy and high-speed machinery.